Reporting system as a predictor for patient safety perception at Primary Health Care Centres - Wijayanti, Erlina; Widianti, Dini; Yusnita; Rifqatussa’adah (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Introduction Incident reporting system is used to capture information on patient safety incidents. The reporting system was used as a way to address patient safety incidents. The implementation of a systematic reporting system reduced the likelihood of adverse events and supported the implementation of patient safety culture. The objectives of the study were to identify correlation between the reporting system and the perception of health workers at Primary Health Care (PHC) Centres. Methods This research was an analytic research with cross sectional study by survey design. The study population was health workers working at PHC Centres in North and Central Jakarta. Sample determination using purposive sampling method. The questionnaire was used to measure variables according to Likert scale. Results This research was attended by 30 respondents. The number of respondents in the <35 years and ≥ 35 years group were even. Respondents’ competency was quite balance in the medical and non-medical groups. Mean of perception 14.1 and median 15. Reporting system (p = 0,048; r = 0,505) correlated significantly with health officer perception about patient safety. Conclusions Reporting system was strong predictor to perception. It was necessary to apply non-blaming culture to address the reporting of patient safety incidents.